Reliability evaluation of substation delivery point with time varying load - Suwantawat P. (2014)
This paper presents a development of substation reliability evaluation by using the sequential Monte Carlo simulation method with time varying load at each delivery point. The technique is illustrated by application to a practical bus arrangement of substation and used to study the sensitivity analysis by varying selected station component parameters. The study results are essential to the condition base maintenance management planning and can play a great role in decision making for improving in main or sub equipment of substation component. It was shown that the Monte Carlo simulation method, which has gained popularity in recent year due to its simplicity and widely use in application to obtain more various indices than analytical method is nearest the real condition of substation, so this approach is a powerful tool for substation reliability evaluation. The results presented in this paper provide valuable information for planning, operation and maintenance of substation.